When the Facts “Call Down Vengeance”. Feeling of Revenge, Sensibiility to Injustices and (A Hint At) Retributive Justice in Scheler’s Formalismus - Roberta Guccinelli (Rosenberg & Sellier, 2016)
The aim of this paper is to provide an elucidation of what, at first sight, appears as a specific and negative affective phenomenon, namely that of revenge, which although its sinister popularity risks constantly to be muddled with a simple state of excitement deprived of intentionality or with a kind of “ justice without justice”. The understanding of the nature of revenge and of impulse of revenge allows to enlighten a peculiar feeling’s class, to which revenge in a certain sense belongs to, and to investigate the meaning and the sense of Scheler’s ambiguous term “Vergeltung” in order to attribute to retributive model of justice, by a comparison with revenge, its correct role and place in the world of Scheler’s. Our back-idea is the one, according to which, refining sensibility to injustices can contribute to a primary form of identity, namely that of our living body.